2016
DOI: 10.15376/biores.11.2.4645-4662
|View full text |Cite
|
Sign up to set email alerts
|

A Response Surface Methodology Study: Effects of Trivalent Cr3+ Metal Ion-Catalyzed Hydrolysis on Nanocellulose Crystallinity and Yield

Abstract: The preparation of nanocellulose via Cr(NO3)3-assisted sulfuric acid hydrolysis was optimized using response surface methodology (RSM). The experiment was performed using a five-level, four-factor central composite design coupled with RSM in order to optimize nanocellulose crystallinity and product yield. Four factors were evaluated for the preparation of nanocellulose: (1) reaction temperature, (2) hydrolysis time, (3) Cr(NO3)3 concentration, and (4) H2SO4 concentration. Based on the RSM model, the maximum yi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…As presented in Figure 3, the FTIR spectra of all the samples exhibited two major absorbance regions, which included the high (3500–2800 cm −1 ) and low wavenumbers (1700–500 cm −1 ) regions, consistent with previous studies [38,39]. A broad and dominant absorbance peak located in the region of 3600 to 3200 cm −1 was observed in all spectra, which corresponded to the characteristic of hydrogen bonding O–H stretching vibrations [40].…”
Section: Resultssupporting
confidence: 89%
“…As presented in Figure 3, the FTIR spectra of all the samples exhibited two major absorbance regions, which included the high (3500–2800 cm −1 ) and low wavenumbers (1700–500 cm −1 ) regions, consistent with previous studies [38,39]. A broad and dominant absorbance peak located in the region of 3600 to 3200 cm −1 was observed in all spectra, which corresponded to the characteristic of hydrogen bonding O–H stretching vibrations [40].…”
Section: Resultssupporting
confidence: 89%
“…The CNCs could be obtained with high yield (83.6% ± 0.6%) when solid-liquid ratio was 1 : 30 and 0.8 M Cr(NO 3 ) 3 was adopted at 80 ∘ C for 1.5 h. The produced CNCs showed a network-like long fibrous structure with the aspect ratio of 15.7. The crystallinity index was 86.5% ± 0.3% and the maximum thermal decomposition temperature was 344 ∘ C. The hydrolysis system of Cr(NO 3 ) 3 -H 2 SO 4 was also investigated by Chen and coworkers [127]. In this work, the maximum yield and highest crystallinity of CNCs were obtained under hydrolysis conditions of 0.22 M Cr(NO 3 ) 3 , 0.80 M H 2 SO 4 , and 82.2 ∘ C within 1 h. Other transition metals were examined as well for catalyzing the hydrolysis of raw cellulose materials to prepare CNCs, such as Fe(III), Al(III), Ni(II), Co(II), and Mn(II) [68,128,129], and they will not be elaborated in detail.…”
Section: Other Methods Some New Methods For the Preparation Of Cncs mentioning
confidence: 99%
“…The peak at 1060 cm -1 corresponded to vibration from the pyranose ring (spectra of NCC) (Wulandari et al 2016). Chen et al (2016) reported that two peaks at 1115 cm -1 and 915 cm -1 corresponded to the C─O─C pyranose ring skeletal vibration and β-linkages, respectively. The FTIR spectroscopy did not explain the chemical interaction between the modifier and PF resin and the effect on its chemical structure, like the case of UF resin modification (Kawalerczyk et al 2020a).…”
Section: Resultsmentioning
confidence: 99%